OP40 Analysis of clinical features associated with favourable outcomes from ustekinumab treat-to-target strategy in Crohn's Disease patients in the STARDUST trial. (27th May 2021) - Danese, S; Vermeire, S; Dignass, A; Panés, J; D'Haens, G; Magro, F; Le Bars, M; Nazar, M; Lahaye, M; Ni, L; Bravatà, I; Gaya, D R; et al.
Abstract: Background: The 48-week (W) interventional STARDUST trial assessed whether a treat-to-target (T 2 T) strategy using ustekinumab (UST) may optimize Crohn's disease (CD) outcomes; primary efficacy and safety data have been reported before. 1 Here we assessed which patient (pt) subgroups may benefit from T 2 T vs standard of care (SoC) in achieving endoscopic response after 1 year of UST treatment. Methods: Adult pts with moderate–severely active CD (CD activity index [CDAI] 220–450) and Simple Endoscopic Score in CD [SES-CD] ≥3) who failed conventional therapy and/or 1 biologic were included. Pts received iv, weight-based UST ~6 mg/kg at W0 (baseline [BL]); then SC UST 90 mg at W8. At W16, CDAI 70 responders were randomized (1:1) to T 2 T or SoC arms. Pts in the T 2 T arm were assigned to SC UST q 12 w or q 8 w based on 25% improvement in SES-CD score vs BL. From W16–48, UST dose was further intensified up to q 4 w if the following were not met: CDAI <220 and ≥70-point improvement from BL, and C-reactive protein ≤10 mg/L or faecal calprotectin (FCal) ≤250 µg/g. Pts who failed treatment target despite UST q 4 w were discontinued. In the SoC arm, UST dose was assigned based on EU SmPC (q 12 w or q 8 w). We report the treatment effect for the primary endpoint (endoscopic response [≥50% improvement in SES-CD score vs BL] at W48), evaluated for subgroups of pts, based on demographics at BL. For each subgroup, the odds ratio (OR) and 95% confidence interval (CI) of T 2 T vs SoC were provided based on the logistic regression model that included treatment arm and stratification factors (prior exposure to biologics [none or 1 ] and SES-CD score [≤16, >  16 ] at BL) as independent variables. Results: Of 500 pts enrolled, 441 were randomized to T 2 T (n=220) or SoC (n=221); 79.1% and 87.3% completed W48. At W48, pts randomized to T 2 T were more likely to achieve endoscopic response compared to SoC (p<0.05), if they had at BL: (i) longer disease duration (>median [79.1 months]; OR 2.2; 95%CI 1.17–3.94); (ii) clinically moderate disease (CDAI ≤300; OR 1.7; 95%CI 1.03–2.76); (iii) normal FCal (≤250; OR 3.0; 95%CI 1.22–7.56), (iv) endoscopically active CD (SES-CD ≥4 for ileal or ≥6 for colonic and/or ileocolonic disease; OR 1.8; 95%CI 1.10–2.91); and (v) history or presence of strictures/fistula or occurrence of an intra-abdominal abscess (OR 2.3; 95%CI 1.06–5.01 and OR 3.5; 95%CI 1.07–11.19, respectively; Figure 1). Conclusion: T 2 T was more effective than SoC (p<0.05) in achieving endoscopic response after 1 year of UST treatment in certain subgroups including pts with higher endoscopic scores at BL and those with history/presence of bowel damage. Reference: Danese S, et al. United European Gastroenterol J. 2020;8:1264–1265 (Abstract LB11).